An approach to the urban history of early Victorian Grahamstown, 1832-53, with particular reference to the interiors and material culture of domestic dwellings - Scott, Patricia Elena (Rhodes University, Faculty of Humanities, Department of History, 1988)
This study is a venture in urban history in that although housing has been the subject of a number of recent studies, little attempt has been made within the British urban history framework to give serious study to what lies behind the architectural facade, the material domestic culture of an urban community. An important objective of this study is to examine the material culture of domestic dwellings in early Victorian Grahamstown, also referring to other parts of the Cape Colony. Where possible these facts are related to the occupants of the dwellings. No community, urban or rural, can be divorced from the influences which lie beyond its immediate locality in region or metropol. As a preliminary to this study the urban background of industrial Britain is examined, as are English and Dutch cultural influences on the interiors of Cape homes in general. The occupational stratification and spatial structure of early Victorian Grahamstown are then explored, leading intoÂ· a discussion of the material domestic culture of the interiors of Grahamstown dwellings. In the final analysis, this study is an attempt to uncover the character of early Victorian Grahamstown and its possible implications for English cultural influences at the Cape. In so doing, not only what constitutes the domestic material culture of Grahamstown is established, but beyond that, a comparison made with domestic material cultural developments in another colonial, though not frontier, settlement with roots in Georgian and Victorian England, namely Australia.
Keywords: Interior decoration -- Grahamstown -- History; Housing -- South Africa -- Grahamstown -- History; Grahamstown (South Africa) -- History